Spatial and temporal variation on distributions of dissolved and particulate arsenic and mercury in Sungai Kuantan, Pahang - Fikriah Faudzi,; Mohd Fuad Miskon,; Kamaruzzaman Yunus,; Mokhlesur Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2017)
It is important to monitor the concentration of toxic metals in the Sungai Kuantan as it serves many communities in terms of domestic, fisheries and agriculture purpose. In order to determine the distributions of dissolved and particulate As and Hg in Sungai Kuantan and evaluate its changes temporally and spatially, water samples were collected from the surface and bottom layers in a grid of 9 stations from estuary towards the upstream of Sungai Kuantan from May 2012 till October 2012. The dissolved metals were pre-concentrated using Chelex-100 while particulate metals were digested using Teflon bomb and subsequently were analyzed using ICP-MS. Dissolved As ranging from 4.650 to 36.894 μg L-1 while dissolved Hg ranging from BDL to 0.011 μg L-1. Particulate As and Hg varied from 0.650 to 86.087 mg L-1 and BDL to 5.873 mg L-1, respectively. Higher concentration of the dissolved elements were found mainly in October 2012 and particulate elements concentration mostly higher in May 2012. The source of the studied metals in the river may be the run-off from the effluent discharges and other natural sources. The toxic elements studied in Sungai Kuantan waters were still below the Interim Marine Water Quality Standard (INWQS) permissible limits.